Comparative study of endonasal dacryocystorhinostomy with and without adjunctive topical use of Mitomycin C - Kulkarni, Ganesh P.; Handal, Ashwini S. (International Journal of Research in Medical Sciences, 2017)
Background: Endoscopic dacryocystorhinostomy has now established itself in the treatment of lacrimal obstruction. Failures in endoscopic dacryocystorhinostomy are mainly due to reclosure of the stoma in the lateral nasal wall. Mitomycin-C is an alkylating agent used in the chemotherapy of various cancers. Mitomycin-C when topically applied to mucosal tissues has been reported to inhibit excessive scar tissue and granulation tissue formation, resulting in greater success rates. Methods: To evaluate the efficacy of Mitomycin-C in preventing reclosure of the dacryocystorhinostomy stoma, we performed a prospective, randomized case control study between November 2013 and October 2015. The study was conducted at tertiary care centre. The study sample consisted of 50 patients, who were randomly assigned to two groups, Group A which received the application of Mitomycin-C topically to the dacryocystorhinostomy stomal site and Group B which did not receive this intervention. The patients were regularly followed up for 6 months. Results: 24 patients (96%) out of 25 in the Group A, had a successful surgical outcome. In Group B 23 patients (92%) out of 25 were symptom free after surgery. These results indicated no statistically significant difference between the two groups (p>0.05). Hence the results of this study did not show any significant benefit for the use of Mitomycin-C as an adjunct during primary endoscopic dacryocystorhinostomy. Conclusions: An atraumatic and meticulous surgical technique along with a good follow up care post-operatively establishes endoscopic dacryocystorhinostomy as an effective treatment modality for chronic dacryocystitis.